2016
DOI: 10.1007/s00184-016-0578-8
|View full text |Cite
|
Sign up to set email alerts
|

Statistical inference for critical continuous state and continuous time branching processes with immigration

Abstract: We study asymptotic behavior of conditional least squares estimators for critical continuous state and continuous time branching processes with immigration based on discrete time (low frequency) observations.Keywords Continuous state and continuous time branching processes with immigration · Branching and immigration mechanisms · Conditional least squares estimator · Non-normal asymptotic limit behaviour Mathematics Subject Classification 62F12 · 60J80

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…see the proof of Theorem 3.4 in Barczy et al[4]), Cv, v > 0 and P Y t dt > 0 = 1, we obtain(3.21).In order to prove(3.22), first note that, under the additional condition Cv, v = 0, we have(4.14) V 0 v, v = 0 if and only if U 2 ν(dz)…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…see the proof of Theorem 3.4 in Barczy et al[4]), Cv, v > 0 and P Y t dt > 0 = 1, we obtain(3.21).In order to prove(3.22), first note that, under the additional condition Cv, v = 0, we have(4.14) V 0 v, v = 0 if and only if U 2 ν(dz)…”
mentioning
confidence: 72%
“…. }, supposing that c, µ and ν are known, Barczy et al [4] derived (non-weighted) CLS estimator ( b n , β n ), of ( b, β), where β := β + ∞ 0 z ν(dz). In the critical case, under some moment assumptions, it has been shown that n( b n − b), β n − β has a non-normal limit.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that, under nearly nonstationarity and assuming finite second moment for ϵt$$ {\epsilon}_t $$, the CLS estimator weakly converges to a normal distribution at the rate n3false/2$$ {n}^{3/2} $$. Other related works dealing with nearly unstable INAR (Galton–Watson/branching) processes are due to Wei and Winnicki (1990), Winnicki (1991), Ispány et al (2005, 2014), Rahimov (2007, 2008, 2009), Drost et al (2009), Barczy et al (2011), Barczy et al (2014, 2016), and Guo and Zhang (2014). Practical situations demonstrating evidence of a nearly unstable INAR model are discussed for instance by Hellström (2001).…”
Section: Introductionmentioning
confidence: 99%
“…They showed that, under nearly non-stationarity and assuming finite second moment for t , the CLS estimator weakly converges to a normal distribution at the rate n 3/2 . Other related works dealing with nearly unstable INAR (Galton-Watson/branching) processes are due to Wei and Winnicki (1990), Winnicki (1991), Ispány, Pap and Van Zuijlen (2005), Rahimov (2007), Rahimov (2008), Drost, Van Den Akker and Werker (2009), Rahimov (2009), Barczy, Ispány and Pap (2011), Ispány, Körmendi and Pap (2014), Barczy, Ispány and Pap (2014), Guo and Zhang (2014), and Barczy, Körmendi and Pap (2016). Practical situations demonstrating evidence of a nearly unstable INAR model are discussed for instance by Hellström (2001).…”
Section: Introductionmentioning
confidence: 99%